Les conflits interétatiques dans les Amériques - Serbin, Andrès (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1986)
This paper introduces two studies on the geopolitics and the conflicts in Latin America. The first part comprises a survey of the conflicts - most of which non-violent - which divide Latin America and oppose its states on an ideological basis, on a finality which would lead to hegemony, on territorial claims, or for reasons due to the impact of migration. The second part deals with the split between the Latin states and the new Anglophone states of the Caribbean, a split which has been bred by the differences in histories, institutions, and political representations, a split which has become apparent in the stands taken, namely in the Falkland crisis and in the border disputes between Venezuela and Guyana, and between Belize and Guatemala.